Percussion Instruments - Jane Beethoven; Rosanne Emery; Silver Burdett Ginn. ([Columbus, OH] Silver Burdett Ginn, 1991)
Viewers see and hear percussion instruments from different parts of the world - - Hear conventional and unusual percussion instruments from Africa, Korea, Indonesia, Brazil, England and the United States - - Discover principles of performance that apply to percussion instruments all over the world - - See an unusual performer who makes music with spoon and forks.
To the Teacher - - Using the Video Library - - Tips on Handling the Tapes - - For Discussion - - General Information - - Questions to Encourage Critical Thinking - - Correlations with THE MUSIC CONNECTION - Student Follow-up - - Vocabulary - - Music Contents - - About the Library.
Series producers : Jane Beethoven; Rosanne Emery.
Keywords: Percussion instruments; Musical instruments